An outlet for Pacific mantle: The Caribbean Sea?. (September 2015) - Nerlich, Rainer; Clark, Stuart R.; Bunge, Hans-Peter
Abstract: The Pacific Ocean is surrounded by subduction zone systems leading to a decreasing surface area as well as sub-surface mantle domain. In contrast, the Atlantic realm is characterized by passive margins and growing in size. To maintain global mass balance, the Caribbean and the Scotia Sea have been proposed as Pacific-to-Atlantic transfer channels for sub-lithospheric shallow mantle. We concentrate on the Caribbean here and test this idea by calculating the present-day regional dynamic topography in search of a gradual decrease from west to east that mirrors the pressure gradient due to the shrinkage of the Pacific. To calculate the dynamic topography, we isostatically correct the observed topography for sediments and crustal thickness variations, and compare the result with those predicted by lithospheric cooling models. The required age-grid was derived from our recently published reconstruction model. Our results confirm previous geochemical and shear-wave splitting studies and suggest some lateral asthenosphere flow away from the Galapagos hotspot. However, they also indicate that this flow is blocked in the Central Caribbean. This observation suggests that rather than through large scale Pacific-to-Atlantic shallow mantle flow, the global mass balance is maintained through some other process, possibly related to the deep mantle underneath Africa.